1973
DOI: 10.1172/jci107465
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assay of a Plasma Factor Deficient in von Willebrand's Disease that is Necessary for Platelet Aggregation. RELATIONSHIP TO FACTOR VIII PROCOAGULANT ACTIVITY AND ANTIGEN CONTENT

Abstract: A B S T R A C T In a previous paper, we showed that the abnormality of ristocetin-induced platelet aggregation in platelet-rich plasma in 10 patients with von Willebrand's disease could be corrected by a factor in normal plasma that was present in the same fractions as factor VIII procoagulant activity (antihemophilic factor, AHF, VIIIAHF) when prepared by chromatography on BioGel 5 M (Bio-Rad Laboratories, Richmond, Calif.). This observation suggests that patients with this disorder are deficient in a plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
168
1
6

Year Published

1975
1975
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(180 citation statements)
references
References 21 publications
5
168
1
6
Order By: Relevance
“…When added to plasma, ristocetin binds VWF, facilitating VWF-GPIb binding in vitro and enabling a quantitative assessment of VWF "activity" by measuring platelet aggregation or agglutination. 33,34 Ristocetin in the presence of plasma VWF significantly decreased platelet electrophoretic mobility, probably because of VWF-platelet interactions promoted by ristocetin. 35 It can also precipitate plasma proteins, including both VWF and fibrinogen.…”
Section: Discussionmentioning
confidence: 96%
“…When added to plasma, ristocetin binds VWF, facilitating VWF-GPIb binding in vitro and enabling a quantitative assessment of VWF "activity" by measuring platelet aggregation or agglutination. 33,34 Ristocetin in the presence of plasma VWF significantly decreased platelet electrophoretic mobility, probably because of VWF-platelet interactions promoted by ristocetin. 35 It can also precipitate plasma proteins, including both VWF and fibrinogen.…”
Section: Discussionmentioning
confidence: 96%
“…Thromboxane B2 was measured in the supernate as described by Lewy et al (27). VIII:C, FVIII-related antigen (VIII:Ag), and VIII:Rcf were assayed by standard methods (26,(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…In severe von Willebrand's disease (vWD), the deficiency of procoagulant and vWF activity (as judged by the ristocetin assay) is associated with a marked deficiency or absence of the F.VIII/vWF protein (7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…In vWD there is usually a good correlation between the procoagulant F. VIII, antigen levels, and the vWF activity as judged by ristocetininduced platelet aggregation (7). To account for these observations it has been suggested that there is a quantitative reduction of a normal protein in von Willebrand's disease while there is a normal amount of an abnormal protein in hemophilia A. Recently four different vWD families have been described in whom some individuals were found to have normal procoagulant F. VIII and antigen levels but defective vWF activity (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%